2007
DOI: 10.1124/mol.107.039792
|View full text |Cite
|
Sign up to set email alerts
|

Docosahexaenoic Acid Induces Increases in [Ca2+]ivia Inositol 1,4,5-Triphosphate Production and Activates Protein Kinase Cγ and -δ via Phosphatidylserine Binding Site: Implication in Apoptosis in U937 Cells

Abstract: We investigated, in monocytic leukemia U937 cells, the effects of docosahexaenoic acid (DHA; 22:6 n-3) on calcium signaling and determined the implication of phospholipase C (PLC) and protein kinase C (PKC) in this pathway. DHA induced dose-dependent increases in [Ca 2ϩ ] i , which were contributed by intracellular pool, via the production of inositol-1,4,5-triphosphate (IP 3 ) and storeoperated Ca 2ϩ (SOC) influx, via opening of Ca 2ϩ release-activated Ca 2ϩ (CRAC) channels. Chemical inhibition of PLC, P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
21
1

Year Published

2008
2008
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(28 citation statements)
references
References 41 publications
(40 reference statements)
6
21
1
Order By: Relevance
“…This result supports previous findings obtained with DHA in our and other laboratories using different cellular models [6,57,58]. However, the molecular factors which may be modulated by DHA in the apoptotic cascades of lung cancer cells remain to be elucidated.…”
Section: Discussionsupporting
confidence: 94%
“…This result supports previous findings obtained with DHA in our and other laboratories using different cellular models [6,57,58]. However, the molecular factors which may be modulated by DHA in the apoptotic cascades of lung cancer cells remain to be elucidated.…”
Section: Discussionsupporting
confidence: 94%
“…Similar results were obtained for different FA, as docosahexaenoic acid (DHA), arachidonic acid (AA) or LA, in several cell lines [30][31][32][33][34]. In addition, according to previous reports, such an increase was found to be concentration-dependent for the three FA tested [30,31].…”
Section: Discussionsupporting
confidence: 73%
“…Subsequently, we investigated CCR3 signaling pathways in terms of calcium mobilization and phosphorylation of ERK. In contrast to a previous report that showed a DHA-induced calcium influx in U937 cells [27], DHA or LA (each 100 µ M ) failed to induce a calcium influx in eosinophils (data not shown). As shown in figure 5b, eotaxin-evoked calcium influx was significantly inhibited by pretreatment with DHA but not by LA.…”
Section: Resultscontrasting
confidence: 52%
“…Therefore, it is suggested that DHA-induced apoptosis is mediated through the caspase-3 pathway, at least in part. Indeed, DHA can activate caspase-3 activity in other types of cells, such as monocytes [29], Jurkat cells [30], and U937 cells [27]. …”
Section: Discussionmentioning
confidence: 99%